Increasing incidence of melanoma after solid organ transplantation: a retrospective epidemiological study. (3rd August 2017) - Fattouh, Kinda; Ducroux, Emilie; Decullier, Evelyne; Kanitakis, Jean; Morelon, Emmanuel; Boissonnat, Pascale; Sebbag, Laurent; Jullien, Denis; Euvrard, Sylvie
Summary: The risk of melanoma in organ transplant recipients (OTR) is increased compared with the general population. This retrospective study registered all cases of post‐transplant melanoma in kidney, heart, lung, and liver transplant recipients followed in our specialized post‐transplant Dermatology Clinic since 1991. The yearly prevalence of melanoma and skin carcinoma between 2000 and 2015 was computed and compared in this population. Based on another cohort of kidney transplant recipients grafted since 2005, adjusted age‐ and sex‐standardized incidence ratio (SIR) was calculated using a renal transplantation registry. In our overall OTR cohort, between 1991 and 2000, five melanomas occurred in 1800 OTRs (0.28%), whereas between 1991 and 2015, 53 melanomas were diagnosed in 49 of 4510 OTR (1.09%), representing a 3.9‐fold increase in prevalence after 2000. Remarkably, the prevalence of nonmelanoma skin cancers remained unchanged over this period. Two deaths related to melanoma were recorded with an overall follow‐up of 62 months. In our cohort of 1102 renal transplant recipients, the SIR of melanoma was 4.52. Our data suggest that contrasting with nonmelanoma skin cancer, the risk of post‐transplant melanoma has considerably increased over the last decade.